Implementasi Pembelajaran Expressing Agreement and Disagreement untuk Meningkatkan Sikap Anti-Perundungan di Sekolah: Penelitian - Rani; Siti Rahmawati; Fara Suseno Putri; Dyah Hanum Palmatiwi; Zaitun Qamariah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study implemented an English learning programme that integrated expressions of agreement and disagreement with an anti-bullying theme to strengthen both speaking skills and students’ social attitudes. Using a descriptive qualitative design, the programme was carried out with 30 eleventh-grade students at a public senior high school. Data were collected through classroom observation, student worksheets, and a questionnaire completed by five purposively selected respondents. The results showed that approximately 97–98% of students demonstrated strong conceptual understanding of the target expressions, and although some initially hesitated to speak spontaneously, their confidence and polite communication improved during discussions on bullying cases. Students were able to identify types of bullying, describe their impacts, propose solutions, and express opinions in English using respectful expressions. Overall, the programme proved that English learning can support character development when connected to real-life social themes, helping students communicate politely while developing anti-bullying awareness.